Exploring the urban consumer's perception of local food. Issue 7 (8th July 2014) - Penney, Ursula; Prior, Caroline
Abstract : Purpose: – The purpose of this paper is to explore the perception and attitudes of urban consumers in the UK towards local food. Design/methodology/approach: – Four focus groups were conducted with participants from Birmingham, UK. A pre-focus group questionnaire was issued to participants to gather demographic data and to provide participants with the "Making Local Food Work" definition of local food. Following on from the focus groups, participants were e-mailed to enquire whether they had any additional comments to provide. Findings: – The results of the study revealed that despite urban consumer interest in local food, this did not necessarily translate in to purchase behaviour. Convenience of the "one-stop" offered by supermarkets along with availability, price and food labelling were found to be key barriers to the purchase of local food. Alternatively, key drivers were identified as freshness, health benefits and improved quality. Research limitations/implications: – The findings are limited with respect to the lack of male participants and younger consumers (pre 45 years old) within the sample whose perceptions of local food may differ from those studied. Practical implications: – Findings support the need for supermarkets to increase their offering of local food for the urban consumer. In addition, supermarkets should improve merchandising, signposting and labelling of local food to encourage increased levels of purchase behaviour from the urban consumer. Originality/value: – The paper explores the somewhat "disconnected" urban consumers' perceptions and attitudes towards local food. On the whole, previous studies of local food have not specifically explored this particular group of consumers.